Physical training strategies for youngsters aged 6-7 years participating in football - Stembridge, David (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. Development and theoretical substantiation of methods of physical training for children aged 6–7 years playing football at the sports and recreational stage. Materials and methods. The study included a cohort of 12 children, aged 6-7 years, who were participants in the sports and leisure program of the Regional Institution of Educational Institution Belarusian State. The content and sequencing of physical training for children aged 6-7 years in football were determined based on data acquired from pedagogical testing in a sports and recreation group. Results. three motor readiness indicators, one physical readiness indicator, and two special motor readiness indicators all showed significant variability (ranging from 54 to 200%). Out of 171 potential interspecies links, the correlation analysis of the abilities of children aged 6 to 7 showed 18 connections. Conclusions. The physical training regimen for children aged 6-7 who play football is designed based on the specific characteristics of their age and unique development of motor, physical, and specialized motor skills ready. The physical training program at the sports and health stage consists of three modules that focus on addressing the issues related to developing fundamental movements, improving lagging physical and special motor qualities, and subsequently enhancing leading physical and special motor qualities.